The Effect of Durian Seed Flour (Durio zibethinus Murr.) addition on Dimensional Stability of Alginate Impression Results - Zahrotus Shobah Isnaini; Aria Fransiska; Didin Kustantiningtyastuti (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Alginate is the most commonly used impression material in dentistry. Alginate impression materials have less dimensional stability if not immediately filled with gypsum. Durian seed flour has the potential to be mixed with alginate because it contains amylose and amylopectin, which play a role in mechanisms of syneresis and imbibition that can affect the dimensional stability of alginate. This research aimed to determine the effect of adding durian seed flour at concentrations of 20% and 40% on the dimensional stability of alginate impressions. Material and Methods: This study was a laboratory experimental research with a pre-and post-test control group design. The total sample was 30. The samples were type III gypsum models made from pure alginate and alginate mixed with durian seed flour, measured at filling times of 0 minutes and 30 minutes. The research data consists of the difference between measurement results of gypsum models at 0 minutes and 30 minutes, which were analyzed by One-way ANOVA and Post Hoc LSD tests. Results and Discussions: The percentage value of dimensional change of all sample groups showed a value below the standard limit of ANSI/ADA Specification No.18, which is 0.5%. One-way ANOVA test showed significant differences (p<0.05). Post Hoc LSD test indicated significant differences between all sample groups (p<0.05). Conclusion: Adding durian seed flour affects the dimensional stability of alginate impressions. Alginate with 40% durian seed flour maintains the dimensional stability of alginate better than pure alginate and alginate with 20% durian seed flour.